Towards realization of high performance electrochemical device using vertically-aligned single-walled carbon nanotubes grown from ethanol - Mohd Abid, Mohd Asyadi Azam (Global Engineers and Technologists Review, 2011)
There has been a growing interest in densely-packed or vertically-aligned (VA-) SWCNTs because of their suitability in energy storage devices such as electrochemical capacitors (ECs) and secondary batteries. Among various methods, the alcohol catalytic chemical vapor deposition (ACCVD) method is a promising one mainly due to its economical merit, wide selectivity of substrates and easy to set-up. Mainly, this research work has significant concerns on VA-SWCNT growth from Co/Al-O based substrates. In ECs, directly growing VA-SWCNTs onto conducting substrate can simplify the fabrication steps (processes), and also might avoid the incorporation of binder material. This, in principle could increase the capacitance behavior and at the same time providing a desired structure of electrode material for better electrolyte ion accessibilities (diffusion, adsorption).